Evaluation of the impact of Monetary Policy on Macroeconomic Stability in Indonesia - Judijanto, Loso; Ikhyanuddin, Ikhyanuddin; Subhaktiyasa, Putu Gede; Lasmiatun, KMT; Jondar , Aloysius (Nomico, 2025)
This study aims to evaluate the effect of monetary policy on macroeconomic stability in Indonesia in the period 2018-2023. Monetary policies implemented by Bank Indonesia, such as changes in benchmark interest rates and controlling the money supply, play an important role in maintaining inflation, exchange rates, and economic growth. Using time series-based quantitative methods, this study analyzed secondary data from Bank Indonesia, the Central Bureau of Statistics, and related international sources. The results showed that monetary policy is effective in controlling inflation and maintaining exchange rate stability, although external challenges such as fluctuations in global commodity prices continue to affect Indonesia's economic performance. Additionally, the study highlights the role of global financial market volatility and geopolitical tensions, which can limit the effectiveness of domestic monetary policies. Despite these challenges, Bank Indonesia's adaptive strategies, including macroprudential measures and policy rate adjustments, have contributed significantly to mitigating negative external shocks. This study provides recommendations for increased coordination between monetary and fiscal policies as well as monetary policy flexibility in facing the challenges of a dynamic global economy. Strengthening institutional frameworks and enhancing transparency in policy communication are also suggested to improve investor confidence and ensure sustainable economic growth.